Influence of mix properties of concrete slabs on the performance of airport pavements. Issue 6 (21st December 2020) - Park, Hae-Won; Kim, Dong-Hyuk; Lee, Jong-Hoon; Yum, Woo-Sung; Jeong, Jin-Hoon
Abstract : Improved criteria for the material properties and mix proportions of concrete slabs to enhance the performance of concrete pavements at Incheon international airport (IA) in the Republic of Korea are suggested. Gimpo IA and Gimhae IA were selected for comparison with Incheon IA based on their facility status and annual flight processing capability. After Incheon IA, Gimpo IA and Gimhae IA have the second and third largest annual numbers of flights per unit area of runway, respectively. Criteria for aggregate and mix proportions were chosen for improvement because of durability cracks (the major form of pavement distress at Incheon IA) due to the poor quality of aggregates used and repeated freeze–thaw cycles. Compared with the other airports, the mix specifications of the concrete slab at Incheon IA showed lower contents of cement and liquid admixture, a higher abrasion rate of coarse aggregate and a larger content of fines in the aggregate. Improved criteria were established based on a comparison of results. Concrete specimens were fabricated using the improved criteria and the performance of the concrete pavement was evaluated by testing the air content and freeze–thaw resistance of 12 mixes with different contents of cement, liquid admixture and fines in the aggregate.